Persepsi Orang Tua Tentang Pendidikan Islam dalam Rumah Tangga di Desa Morella, Kabupaten Maluku Tengah, Indonesia - Saida Manilet (DAYAH: Journal of Islamic Education, 2021)
The research is here to study parents' perceptions in Morella Village, Central Maluku Regency, about Islamic education for children in the household. The research method is a qualitative description. The data source is chosen using the purposive sampling technique—data collected by interview, observation, and collection techniques. Data analysis is performed by data reduction, data display, and data verification. The results of the study found about parents' perceptions about Islamic education for children in the household, prayer requests, reading / reading the Holy Qur'an, teaching children to be diligent in school, and responding to neighbours and the community. Islamic education for parents only needs to be improved when children aged 4-12 years. In contrast, adolescent children no longer need to be improved because they must have the awareness to behave.